2005
DOI: 10.1002/chin.200549229
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Magnetism in Carbon Based Materials

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Most known bulk modifications of carbon, as ordered graphite and diamond with negligible concentration of intrinsic defects, exhibit a pronounced diamagnetism [1,2,5]. However, introduction of additional defects has shown that the material acquires FM-like properties, which takes place e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most known bulk modifications of carbon, as ordered graphite and diamond with negligible concentration of intrinsic defects, exhibit a pronounced diamagnetism [1,2,5]. However, introduction of additional defects has shown that the material acquires FM-like properties, which takes place e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A broad variety of carbon-based materials attracts attention due to unusual magnetic properties, including ferromagnetic (FM) behavior with evidence for a possibility of a long-range magnetic order [1,2]. Some of them are characterized by FM Curie temperature, T C , lying above the room temperature [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes them attractive for applications not only in techniques, but in biology and medicine as well, being low-toxic due to vanishing concentrations of metallic elements [1,2]. Generally, residual metallic impurities have been proved to play a negligible role in formation of the observed FM signal [13].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, residual metallic impurities have been proved to play a negligible role in formation of the observed FM signal [13]. Therefore, the unconventional magnetism of carbon-based materials is associated with intrinsic defects or disorder introduced into an ordered host matrix [1,2], which exhibits only a diamagnetic response as takes place in bulk ordered graphite and diamond [13]. In contrast, intentional incorporation of defects in graphite e. g. by proton irradiation leads to a pronounced ferromagnetism [2,5,6].…”
Section: Introductionmentioning
confidence: 99%